Mechanical and Fractured surface characterization of epoxy/red mud/fly ash/ aluminium powder filled hybrid composites for automotive applications (Fracture and Structural Integrity, 2023)
In recent decades, one can observe a great increase in the replacement of traditional materials with polymer composites in high-strength and lightweight applications. High fuel consumption by automobile and aerospace vehicles built from legacy alloys has been a great challenge to material engineers. This has called for researches into lighter material development of the same or even superior mechanical properties to the existing materials in this area of applications. In the present study, epoxy based simple and hybrid composites were prepared with the incorporation of industrial waste as fillers at different weight percentages. Effect of filler type, combination and its concentration on mechanical properties such as tensile, impact and flexural strength were investigated. SEM analysis was carried out for fractured surfaces of composites, wherein minor voids, crack initiations and filler pullouts were seen indicating the necessity of coupling agent addition for still better performance. Among hybrid composites, epoxy/fly ash/red mud/aluminium powder (91/6/1.5/1.5 wt%) has showed the highest ultimate tensile modulus, flexural strength and hardness value compared to other composites under study.
Keywords: Epoxy; Red mud; Fly ash; Aluminium powder; Hybrid composite